Tensiones medievales entre iglesia y estado: una mirada desde Tomas de Aquino (2020)
The purpose of this article is to review the link between the thought of Thomas Aquinas in the theological-political problems that are going through his time, since the so-called "Investiture Controversy" and its resolution in the Worms concordat of 1122. For this, we will trace some fundamental elements of medieval law and its relation to the problem of the relationship between the eternal law, the natural law and human law. It is proposed to defend the idea that the Angelic Doctor resists becoming a point of articulation between a medieval and a modern conception of State, that begins to dazzle the latter of the tutelage of the Church, to rescue its own legitimacy in the search for the common Good.